Production of a $^{76}$Kr radioactive ion beam using a batch mode method - Cooper, J.R.; Bernstein, L.; McMahan, M.A.; Powell, J.; Wutte, D.; Ahle, L.; Benczer-Koller, N.; Dashdorj, D.; Kumbartzki, G.; Mertzimekis, T. J.; Schiller, A.; Silver, C.; et al. (Nucl. Instrum. Meth. Phys. Res. A, 2004)
A batch mode process has been developed to produce a 76Kr (T1/2 = 14.8 h) radioactive ion beam at the Lawrence Berkeley National Laboratory 88-in. Cyclotron. First, a 6 particle ?A ? beam is run for 17 h to produce approximately 101476Kr atoms via the reaction 74Se(?, 2n)76Kr. Then, the krypton is separated from the target material and injected into the AECR-U ion source. Beam intensities as high as 3 × 108 particles per second are observed with an integrated beam current of 6(2) × 1011 particles per 24-h batch cycle. © 2004 Published by Elsevier B.V.
Keywords: 74se; 76kr; Batch mode; Batch mode method; Cyclotrons; Diffusion; Gas transfer system; Ion beams; Ion sources; Kinematics; Krypton; Nitrogen; Radioactive beams beams; Radioactive heavy ion beam; Re-cyclotron